PERANCANGAN PADA FPGA ATAS MODEL PENGIRIM SINGLE CARRIER FREQUENCY DIVISION MULTIPLE ACCESS (SC-FDMA) - , PAMUNGKAS BAGASKARA NUGROHO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
SC-FDMA is a multiple-access technique which is a modified version of OFDMA OFDMA is a multicarrier multiple-access technique which is able to provide parallel transmission service with high bit rate and very efficient in bandwidth usage and used in LTE downlink. SC-FDMA designed to minimize OFDMAâs weakness in power efficiency, so it suitable to be implemenedt in LTE uplink. The objective of this study is to implement a model of SC-FDMA transmitter on a Xilinx Spartan-3E FPGA chip. Design is divided into sections that include QPSK mapper, FFT, IFFT, and parallel to serial converter. The design is created with VHDL in Xilinx ISE 9.2i software. The output of SC-FDMA transmitter is displayed on LCD interface on Xilinx Spartan-3E development board and compared with output of similar SC-FDMA transmitter modeled in Excel and Matlab. As a result, the implementation of SC-FDMA transmitter is able to show true performance and very close to the result of Matlab. In terms of capacity, Xilinx Spartan-3E FPGA is sufficient for the needs of the design.